The Dynamics of Relationship Between Legislative and Executive in Post Reformation Era: A Critical Thinking for Amendment of the 1945 Constitution - Sunarto Sunarto (Politik Indonesia: Indonesian Political Science Review)
Amendment of the 1945 Constitution brought significant shifting on the Indonesian government. Before amendment, the government was dominated by the enormous power of President (executive heavy). The amendment strengthens the DPR’s power realizing the checks and balances between DPR and President. The amendment of the 1945 Constitution also brought the purification of presidential system. These two things make the dynamics of relationship between the DPR and the President. In post amendments, the government is characterized by an increasing controlling function of DPR. But the combination of presidential system and the multi-party still brings problem related to government instability. Relationship between the DPR and the President was strongly influenced by the presence of opposition parties, which in the previous was regarded as “a taboo” in Indonesian democracy. On the other hand, the elected president also became a strong magnet to get the support of political parties in DPR. Therefore, certain parties that previously became the government’s opposition crossed and supported government. Thus, the presumption that the elected President would find difficulties in implementing his policies because of the lack of support in the DPR was not proven.